Effect of Varied Dribbling Training on Agility and Ball Control among Physical Education Students at Universitas Muhammadiyah Luwuk Banggai - Jamaludin Bahtiar Gui, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study investigated the effect of varied dribbling training on agility and ball control among physical education students at Universitas Muhammadiyah Luwuk BanggaiMaterials and Methods.  A quasi experimental approach with a pretest posttest design was applied to physical education students who participated in a structured varied dribbling training program, agility was assessed using a standard agility test and ball control was assessed using a football dribbling or ball control test, data were analyzed to compare changes from pretest to posttest and differences between the training and comparison groups with a significance level of alpha 0 05Results.  The results showed that varied dribbling training significantly improved agility and ball control from pretest to posttest with p less than 0 05, improvements in the training group were greater than those in the comparison group, indicating meaningful effects with effect sizes in the moderate to large rangeConclusions. Varied dribbling training is effective for improving agility and ball control in university physical education students and can be recommended as a structured component of football skill development programs